Two-Step Bio-Oil Upgrading Using Carbon-Supported Mo2C Catalysts - Wang, Haiyan; Liu, Shida; Dai, Yiling; Kim, Chang Soo; Smith, Kevin J. (American Chemical Society, 2024)
Bio-oils are thermally unstable with high acidity, viscosity, and low heating value. Hence, crude bio-oils must be upgraded to obtain a product that meets current fuel standards while minimizing coke formation and catalyst deactivation. This study combined esterification and hydrodeoxygenation (HDO) in a two-step process to obtain an upgraded bio-oil. Mo2C-based catalysts had sufficient acidity to generate esters and stabilize the bio-oil. Among them, 2Ni-Mo2C/ABC (ABC & horbar;activated biochar) performed better because of a high hydrogenation activity. In the subsequent HDO step, the best Mo2C-based catalyst achieved 69% HDO with an overall carbon yield of 67%. The results are comparable to the one-step HDO using a Pd/C catalyst but offer the use of a lower-cost catalyst and reduced coke formation.